Caveolin-1 Promotes Chemoresistance of Gastric Cancer Cells to Cisplatin by Activating WNT/β-Catenin Pathway - Wang, Xi; Lu, Bin; Dai, Chunyan; Fu, Yufei; Hao, Ke; Zhao, Bing; Chen, Zhe; Fu, Li (Frontiers in Oncology, 2020)
Drug resistance is a major challenge for chemotherapy in treating human gastric cancer (GC), as the underlying molecular mechanism of chemoresistance in GC remains unknown. Caveolin-1 (Cav-1) is a scaffold protein of plasma membrane caveolae that acts as a tumor modulator by interacting with several cell signals. In this research, we showed that the survival rate of GC cells to cisplatin (CDDP) increased in the presence of Cav-1. Moreover, Cav-1 overexpression inhibited cisplatin-induced apoptosis and improved the survival rate of GC cells. Cav-1 overexpression and knock-down experiments indicated that Cav-1 expression stimulated wingless-type MMTV integration site (WNTs) pathway through the phosphorylation of LRP6 and dephosphorylation of β-catenin. Cav-1 was positively associated with the increase of WNT downstream target gene Met, which led to the activation of HER2 signaling. Moreover, our results demonstrated that the expression of Cav-1 and Met were positively associated with the resistance of GC cells to cisplatin. Collectively, Cav-1 enhances the cisplatin-resistance of GC cells by activating the WNT signaling pathway and Met-HER2 crosstalk. Understanding the role of Cav-1 in the chemoresistance of GC would help to develop novel therapies for a better treatment outcome of GC patients.